Metadichol Treatment of Fibroblasts and Embryonic Stem Cells Regulates Key Cardiac Progenitors - Raghavan, Palayakotai R. (Cardiology and Cardiovascular Medicine, 2023)
Background: Heart disease has been identified as one of the main causes of heart attack; moreover, it is known to result in the death of billions of cardiomyocytes, which cannot be reproduced and replaced. The remaining cells are often faced with a significant increase in hemodynamic burden. Repairing the heart after an attack or other cardiovascular disease has eluded medical science. The ability to repair the heart muscles using the own cells of a patient who had suffered from a heart attack is a long-sought goal to regenerate healthy new tissues. Cell sources for cardiac disease treatment include human embryonic stem cells (hESCs), which are known to have the capacity to differentiate into chondrocytes, osteoblasts, adipocytes, and cardiomyocytes. Cardiac fibroblasts are present in large numbers in the heart; they are known to be involved in the repair of the structural, biochemical, mechanical, and electrical properties of the myocardium. Methods: Here, we present the use of Metadichol for the treatment of hESCs and human cardiac fibroblasts, wherein it resulted in the increase in the expression of the key cardiac progenitors ISL1, NKX2-5, and GATA4, WT-1, KIT, determined to be crucial in heart development. We characterized their mRNA expression by qRT-PCR and protein expression by Western blot. Results: Treating hESCs with Metadichol at a concentration of 1 nanogram for 24 h has led to the enhanced gene expression of ISL1 (67-fold), GATA4 (7.5-fold), NXK2-5 (4.35-fold), Kit (10.41-fold) and WT1(4.99-fold). In human cardiac fibroblasts treated with 100 picogram of Metadichol, increases of ISL1 (1.77-fold), NKX2-5 (19.82-fold), and GATA4 (19.9- fold) kit (12.23-fold) and WT1(1.87-fold) were seen. Conclusions: These cardiac progenitors play a role in heart diseases, especially ISL1, which has been suggested to be a single source for the heart lineages and its development. Given the fact that Metadichol is nontoxic and safe it can be directly tested in humans skipping other procedures being employed today and improvements monitored non-invasively. possibility of the direct use of Metadichol in patients with heart disease, as it has no known toxicity and is commercially available and marketed worldwide.